Beyond surfing: Diversification opportunities in coastal sport tourism in Pesisir Barat, Lampung - Galih Bayu Suseno; Agus Kristiyanto; Sugiyanto (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2026)
This study examines how diversification opportunities beyond surfing are experienced and interpreted by tourism actors in the development of coastal sport tourism in Pesisir Barat. Method: A qualitative phenomenological approach was used through in-depth interviews, participant observation, and document review conducted across Tanjung Setia, Labuhan Jukung, Mandiri, and Pulau Pisang. Nine informants representing business actors, sport communities, government agencies, media promotion, and local residents were involved. Findings: The findings show that diversification is emerging through beach-based activities such as fun runs and beach volleyball, calm-water marine opportunities such as snorkeling and related marine trips, and land-based nature extensions such as jungle trekking and waterfall visits. However, these opportunities remain uneven and conditional because their feasibility depends on safety systems, community-based organizers, basic infrastructure, realistic seasonal reading, and stronger governance coordination. Conclusion: Beyond-surfing development should not be understood as a replacement of the surfing core, but as a selective destination portfolio strategy that can widen tourist demand, extend local value creation, and strengthen coastal tourism resilience.